2023
DOI: 10.1002/pen.26248
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of ultrafine non‐hydrolyzed silk sericin/PEO fibers on PLA: A bilayer scaffold fabrication

Abstract: We report the feasibility of electrospinning of protein-polymer multilayered scaffolds with selected materials such as non-hydrolyzed silk sericin (SS), polyethylene oxide (PEO), and polylactic acid (PLA), with tuned fiber size and properties for each layer. We present a new innovative way for the electrospinning (ES) of non-hydrolyzed SS mixed with PEO yielding fibers with an average diameter ranging between 120 and 150 nm. Different SS:PEO ratios have been electrospun to study the effect of the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[4][5][6] Electrospinning, as an effective technique in the production of nanofibers, is widely used since the produced fibers have a uniform appearance. 7,8 A large number of natural or synthetic macromolecules, such as PVA, 9,10 poly(ε-caprolactone), 11 poly(lactic acid), 12 collagen, 13 gelatin, 14 and chitosan, 15 have been successfully fabricated into composite fiber mats for biomedical purpose.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Electrospinning, as an effective technique in the production of nanofibers, is widely used since the produced fibers have a uniform appearance. 7,8 A large number of natural or synthetic macromolecules, such as PVA, 9,10 poly(ε-caprolactone), 11 poly(lactic acid), 12 collagen, 13 gelatin, 14 and chitosan, 15 have been successfully fabricated into composite fiber mats for biomedical purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 18 investigated the printability of PEO solutions with different mass fractions and demonstrated the ability to print various patterns using EHD printing, achieving an accuracy of around a dozen micrometers. Mathieu et al 19 demonstrated the feasibility of electrospinning protein polymer multiple scaffolds using SS/PEO electrospinning on PLA. Carrasco et al 20 used electrospinning to prepare poly(ethylene‐b‐ethylene oxide) block copolymer (PE‐b‐PEO) fibers.…”
Section: Introductionmentioning
confidence: 99%